Highly Thermo-Conductive Three-Dimensional Graphene Aqueous Medium - Bo, Zheng; Ying, Chongyan; Yang, Huachao; Wu, Shenghao; Yang, Jinyuan; Kong, Jing; Yang, Shiling; Zhou, Yanguang; Yan, Jianhua; Cen, Kefa (Nano-Micro Letters, 2020)
Highly thermo-conductive aqueous medium is a crucial premise to demonstrate high-performance thermal-related applications. Graphene has the diamond comparable thermal conductivity, while the intrinsic two-dimensional reality will result in strong anisotropic thermal conductivity and wrinkles or even crumples that significantly sacrifices its inherent properties in practical applications. One strategy to overcome this is to use three-dimensional (3D) architecture of graphene. Herein, 3D graphene structure with covalent-bonding nanofins (3D-GS-CBF) is proposed, which is then used as the filler to demonstrate effective aqueous medium. The thermal conductivity and thermal conductivity enhancement efficiency of 3D-GS-CBF (0.26 vol%) aqueous medium can be as high as 2.61 W m−1 K−1 and 1300%, respectively, around six times larger than highest value of the existed aqueous mediums. Meanwhile, 3D-GS-CBF can be stable in the solution even after 6 months, addressing the instability issues of conventional graphene networks. A multiscale modeling including non-equilibrium molecular dynamics simulations and heat conduction model is applied to interpret experimental results. 3D-GS-CBF aqueous medium can largely improve the solar vapor evaporation rate (by 1.5 times) that are even comparable to the interfacial heating system; meanwhile, its cooling performance is also superior to commercial coolant in thermal management applications. Highlights: 1 3D graphene structure with covalent-bonding nanofins is proposed to demonstrate highly thermo-conductive aqueous medium. 2 An ultralow loading of 3D graphene enables aqueous medium with a record high thermal conductivity of 2.61 W m−1 K−1. 3 3D graphene aqueous medium can remarkably enhance the performance of solar thermal conversion and heat dissipation.